LIBIDO AND EJACULATE CHARACTERISTICS OF BOARS EXPOSED TO DIRECT SOLAR RADIATION - F. C. Elile; C. C. Ogbu; S. O. C. Ugwu; N. S. Machebe (Journal of Animal and Plant Sciences, 2014)
The study was carried out to determine the semen characteristics: volumes of ejaculate (VEJ), gel fraction (VGF) and strained ejaculate (VSEJ), sperm concentration (SPC), progressive motility (PGM), live spermatozoa (LVS), abnormal spermatozoa (ABS) and pH (SpH)] as well as the reaction time (RT) and ejaculation time (EJT) of Large White (LW) and Large White x native (LW x N) F1 crossbred (CR) boars exposed to direct solar radiation. A total of 24 grower-finisher boars (12/genotype) aged 6 months and of mean body weight 50.14 kg for LW and 46.65 kg for CR were used for the study. The study involved three treatments (8 boars/treatment; 4 boars/replicate) made up of control (T1); 45 min. (T2) and 60 min. (T3) exposures. Boars in T1 were reared intensively while those of T2 and T3 were exposed in outdoor paddocks. A 14 day pre-experimental period was observed for adaptation and to train the boars for semen collection using a dummy and artificial vagina. Mean indoor and outdoor ambient temperatures differed significantly (P ≤ 0.01) (range: 27.2 to 28.5 oC and 39.9 to 41.06 oC, respectively). Result showed significant (P ≤ 0.05) effects of genotype, duration of exposure and genotype x duration of exposure on most of the semen quality traits while volume of gel fraction (VGF), SpH, RT and EJT were less affected. Generally, the crossbred (CR) genotype maintain better semen quality than the LW genotype over the experimental period. It was suggested that crossbreeding involving heat tolerant indigenous breeds and highly performing exotic breeds of pigs should be undertaken to develop swine breeds that combine thermal tolerance with high performance for improved pig production in Nigeria.
Keywords: Crossbred; large white; semen traits; solar radiation; thermal stress; thermo-neutral zone